Hydrothermal self-assembly of graphene foams with controllable pore size. Issue 25 (19th February 2016) - Deng, Wei; Fang, Qile; Zhou, Xufeng; Cao, Hailiang; Liu, Zhaoping
Abstract : Graphene foams with controllable pore size are fabricated by facile one-step hydrothermal self-assembly by altering the sheet sizes of GO, and uniform pore sizes as small as ∼500 nm can be successfully realized. Abstract : Pore size is a critical parameter that affects the basic physicochemical properties and applications of porous graphene foam, but the preparation of graphene foam with controllable pore size is still a big challenge, especially by a self-assembly method. In this work, graphene oxide (GO) sheets with different lateral sizes by controlling the delamination conditions of graphite oxide were used as building blocks to form graphene foams with adjustable pore size, by a convenient one-step hydrothermal self-assembly method. The pore sizes of graphene foams can be effectively controlled by simply altering the sheet sizes of GO, and the smallest average pore size is ∼500 nm, which is much smaller than the micrometer-scale pores in the reported graphene foam materials. Static contact angles, nitrogen adsorption–desorption isotherms and adsorption of methylene blue are measured to demonstrate the strong dependence of some important physicochemical properties of graphene foams on their pore sizes. This simple method offers a novel way to rationally synthesize graphene foam with appropriate pore size for various practical applications.